TNFα enhances force generation in airway smooth muscle - Dogan, Murat (Am J Physiol Lung Cell Mol Physiol, 2017)
Airway inflammation is a hallmark of asthma, triggering airway smooth muscle (ASM) hyperreactivity and airway remodeling. TNFα increases both agonist-induced cytosolic Ca(2+) concentration ([Ca(2+)](cyt)) and force in ASM. The effects of TNFα on ASM force may also be due to an increase in Ca(2+) sensitivity, cytoskeletal remodeling, and/or changes in contractile protein content. We hypothesized that 24 h of exposure to TNFα increases ASM force by changing actin and myosin heavy chain (MyHC) content and/or polymerization. Porcine ASM strips were permeabilized with 10% Triton X-100, and force was measured in response to increasing concentrations of Ca(2+) (pCa 9.0 to 4.0) in control and TNFα-treated groups. Relative phosphorylation of the regulatory myosin light chain (p-MLC) and total actin, MLC, and MyHC concentrations were quantified at pCa 9.0, 6.1, and 4.0. Actin polymerization was quantified by the ratio of filamentous to globular actin at pCa 9.0 and 4.0. For determination of total cross-bridge formation, isometric ATP hydrolysis rate at pCa 4.0 was measured using an enzyme-coupled NADH-linked fluorometric technique. Exposure to TNFα significantly increased force across the range of Ca(2+) activation but did not affect the intrinsic Ca(2+) sensitivity of force generation. The TNFα-induced increase in ASM force was associated with an increase in total actin, MLC, and MyHC content, as well as an increase in actin polymerization and an increase in maximum isometric ATP hydrolysis rate. The results of this study support our hypothesis that TNFα increases force generation in ASM by increasing the number of contractile units (actin-myosin content) contributing to force generation.